Optical glass, glass preform and optical element

By optimizing the component design of optical glass, it contains components such as SiO2, ZrO2, BaO, CaO, TiO2 and ZnO, the problem of insufficient internal quality and weather resistance of optical glass is solved, and high-performance optical glass is realized, suitable for large-diameter lenses and harsh environments.

CN119118503APending Publication Date: 2024-12-13CDGM OPTICAL GLASS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310696552.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing optical glass has internal quality problems in large-diameter applications, such as insufficient bubbles and weather resistance, which makes it difficult to meet the harsh environmental needs in the fields of vehicle-mounted and monitoring.

Method used

By optimizing the component design, it contains components such as SiO2, ZrO2, BaO, CaO, TiO2 and ZnO. The ratio of (TiO2+ZnO)/CaO is controlled within the range of 0.6 to 8.0, the refractive index is 1.64 to 1.695, and the Abbe number is 45.5 ~51.5, weather resistance CR is 2 or above, and bubble degree is 3 or above.

Benefits of technology

It achieves the improvement of the internal quality and excellent weather resistance of optical glass, extends the service life of the glass in harsh environments, and meets the high performance requirements of large-diameter lenses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004281956790000121
    Figure BDA0004281956790000121
  • Figure BDA0004281956790000151
    Figure BDA0004281956790000151
  • Figure BDA0004281956790000161
    Figure BDA0004281956790000161
Patent Text Reader

Abstract

The invention provides optical glass which comprises the following components in percentage by weight: 0.6-8.0% of SiO2, ZrO2, BaO, CaO, TiO2 and ZnO, the refractive index nd of the optical glass is 1.64-1.695, the Abbe number vd of the optical glass is 45.5-51.5, the weather resistance CR of the optical glass is more than 2 classes, and the bubble degree of the optical glass is more than A class. Through reasonable component design, the optical glass has excellent weather resistance and internal quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an optical glass, in particular to an optical glass with high internal quality and excellent weather resistance. Background Art

[0002] In recent years, as vehicle-mounted and security lenses develop towards large-caliber and high-definition directions, the corresponding requirements are for optical lenses to have larger diameters. For example, in the design of smart car lights, the diameter of the lens needs to be increased from the traditional 15 to 25 mm to about 45 to 60 mm. The substantial increase in the diameter of the lens requires the glass material to have excellent internal quality (such as stripes, bubbles, etc.). If the components of the optical glass are not designed reasonably, it is easy to cause a large number of bubbles in the glass, causing the glass to be scrapped. On the other hand, optical glass used in monitoring, vehicle-mounted and other fields requires excellent weather resistance to extend the service life of the optical glass in harsh environments. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide an optical glass with high internal quality and excellent weather resistance.

[0004] The technical solution adopted by the present invention to solve the technical problem is:

[0005] Optical glass, comprising SiO2, ZrO2, BaO, CaO, TiO2 and ZnO, wherein the components are expressed in weight percentage, wherein (TiO2+ZnO) / CaO is 0.6 to 8.0, and the refractive index of the optical glass is n d 1.64~1.695, Abbe number ν d The temperature is 45.5-51.5, the weather resistance CR is 2 or above, and the bubble degree is A or above.

[0006] Furthermore, the optical glass, expressed in weight percentage, contains: SiO2: 26-36%; and / or Al2O3: 0-8%; and / or ZrO2: 1-10%; and / or BaO: 32-43%; and / or CaO: 2-10%; and / or SrO: 0.1-7%; and / or TiO2: 0.1-6%; and / or ZnO: 5-15%; and / or Na2O: 0.1-7%; and / or B2O3: 0-6% ; and / or MgO: 0-5%; and / or Li2O: 0-5%; and / or K2O: 0-5%; and / or WO3: 0-5%; and / or Nb2O5: 0-5%; and / or Ln2O3: 0-5%; and / or clarifier: 0-1%, wherein Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.

[0007] Optical glass, the components of which are expressed in weight percentage, are SiO2: 26-36%; Al2O3: 0-8%; ZrO2: 1-10%; BaO: 32-43%; CaO: 2-10%; SrO: 0.1-7%; TiO2: 0.1-6%; ZnO: 5-15%; Na2O: 0.1-7%; B2O3: 0-6%; MgO: 0-5%; Li2O: 0-5%; K2 O: 0-5%; WO3: 0-5%; Nb2O5: 0-5%; Ln2O3: 0-5%; clarifier: 0-1%, wherein (TiO2+ZnO) / CaO is 0.6-8.0, the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, Lu2O3, and the clarifier is one or more of Sb2O3, SnO, SnO2, CeO2.

[0008] Furthermore, the optical glass, whose components are expressed in weight percentage, satisfies one or more of the following 11 conditions:

[0009] 1) TiO2 / (CaO+Al2O3) is 0.01 to 1.5, preferably TiO2 / (CaO+Al2O3) is 0.05 to 1.0, more preferably TiO2 / (CaO+Al2O3) is 0.1 to 0.8, and further preferably TiO2 / (CaO+Al2O3) is 0.1 to 0.5;

[0010] 2) (SiO2 + SrO) / TiO2 is 4.5 or more, preferably (SiO2 + SrO) / TiO2 is 5.0 or more, more preferably (SiO2 + SrO) / TiO2 is 6.0 to 32.0, and further preferably (SiO2 + SrO) / TiO2 is 7.5 to 20.0;

[0011] 3) (CaO + SrO) / ZnO is 0.2 to 2.0, preferably (CaO + SrO) / ZnO is 0.4 to 1.5, more preferably (CaO + SrO) / ZnO is 0.5 to 1.2, and further preferably (CaO + SrO) / ZnO is 0.7 to 1.0;

[0012] 4) (TiO2+ZnO) / CaO is 0.8 to 5.0, preferably (TiO2+ZnO) / CaO is 1.0 to 4.0, and more preferably (TiO2+ZnO) / CaO is 1.5 to 3.0;

[0013] 5) B2O3 / Na2O is 8.0 or less, preferably B2O3 / Na2O is 0.05 to 5.0, more preferably B2O3 / Na2O is 0.1 to 4.0, and further preferably B2O3 / Na2O is 0.2 to 2.0;

[0014] 6) TiO2 / Na2O is 0.02 to 5.0, preferably TiO2 / Na2O is 0.05 to 3.0, more preferably TiO2 / Na2O is 0.1 to 2.0, and further preferably TiO2 / Na2O is 0.3 to 1.5;

[0015] 7) SiO2 / (Na2O+BaO) is 0.55 to 0.95, preferably SiO2 / (Na2O+BaO) is 0.55 to 0.9, more preferably SiO2 / (Na2O+BaO) is 0.6 to 0.85, and further preferably SiO2 / (Na2O+BaO) is 0.65 to 0.8;

[0016] 8) BaO / (SiO2+B2O3+TiO2+Li2O) is 0.65 to 1.2, preferably BaO / (SiO2+B2O3+TiO2+Li2O) is 0.7 to 1.1, more preferably BaO / (SiO2+B2O3+TiO2+Li2O) is 0.75 to 1.05, and further preferably BaO / (SiO2+B2O3+TiO2+Li2O) is 0.8 to 1.05;

[0017] 9) (SiO2+BaO) / (Li2O+Na2O+K2O+TiO2) is 6.0 or more, preferably (SiO2+BaO) / (Li2O+Na2O+K2O+TiO2) is 8.3 or more, more preferably (SiO2+BaO) / (Li2O+Na2O+K2O+TiO2) is 9.0 to 50.0, and further preferably (SiO2+BaO) / (Li2O+Na2O+K2O+TiO2) is 10.0 to 30.0;

[0018] 10) Ln2O3 / TiO2 is less than 0.5, preferably Ln2O3 / TiO2 is less than 0.4, more preferably Ln2O3 / TiO2 is less than 0.3, and further preferably Ln2O3 / TiO2 is less than 0.1;

[0019] 11) (B2O3+Ln2O3) / ZrO2 is less than 1.8, preferably (B2O3+Ln2O3) / ZrO2 is less than 1.5, more preferably (B2O3+Ln2O3) / ZrO2 is 0.05~1.2, and further preferably (B2O3+Ln2O3) / ZrO2 is 0.1~1.0, and the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3.

[0020] Furthermore, the optical glass, its components are expressed in weight percentage, wherein: SiO2: 28-34%, preferably SiO2: 29-31%; and / or Al2O3: 1-7%, preferably Al2O3: 2-5%; and / or ZrO2: 2-8%, preferably ZrO2: 3-6%; and / or BaO: 34-42%, preferably BaO: 36-40%; and / or CaO: 3-8%, preferably CaO: 4-7%; and / or SrO: 0.5-5%, preferably SrO: 1-4%; and / or TiO2: 0.5-5%, preferably TiO2: 0.5-4%; and / or ZnO: 7-13%, preferably ZnO: 9-12%; and / or Na2O: 1-6%, preferably Na2O: 2-5%; and / or B2O3: 0.5-5%, preferably B2O3: 1-3%; and / or MgO: 0-3%, preferably MgO: 0-1%; and / or Li2O: 0-2%, preferably Li2O: 0-1%; and / or K2O: 0-2%, preferably K2O: 0-1%; and / or WO3: 0-2%, preferably WO3: 0-1%; and / or Nb2O5: 0-2%, preferably Nb2O5: 0-1%; and / or Ln2O3: 0-2%, preferably Ln2O3: 0-1%; and / or clarifier: 0-0.5%, preferably clarifier: 0-0.2%, wherein Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3, and the clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2.

[0021] Furthermore, the optical glass does not contain MgO in its components; and / or does not contain Li2O; and / or does not contain K2O; and / or does not contain WO3; and / or does not contain Nb2O5; and / or does not contain SnO2; and / or does not contain SnO; and / or does not contain CeO2; and / or does not contain As2O3; and / or does not contain PbO; and / or does not contain Ln2O3, and the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3.

[0022] Furthermore, the refractive index n of the optical glass is d is 1.64 to 1.695, preferably 1.65 to 1.69, more preferably 1.66 to 1.68, and the Abbe number v d It is 45.5-51.5, preferably 46-50, more preferably 47-49.

[0023] Furthermore, the density of the optical glass is 4.00 g / cm 3 Below, preferably 3.90g / cm 3 Below, more preferably 3.85g / cm 3Below; and / or thermal expansion coefficient α 100 / 300℃ 100×10 -7 / K or less, preferably 98×10 -7 / K or less, more preferably 95×10 -7 / K or less; and / or water resistance stability D W The weather resistance is CR of Class 2 or more, preferably Class 1 or more; and / or the air bubble degree is Class A or more, preferably Class A0 or more, more preferably Class A or more. 00 level; and / or transition temperature T g 660°C or less, preferably 650°C or less, more preferably 640°C or less; and / or the striae is C or above, preferably B or above; and / or the viscosity at 1400°C is 60 poise or less, preferably 1 to 50 poise, more preferably 2 to 30 poise; and / or the light transmittance τ 400nm It is 95.0% or more, preferably 96.0% or more, more preferably 97.0% or more, and further preferably 98.0% or more.

[0024] The glass preform is made of the above optical glass.

[0025] The optical element is made of the above optical glass, or made of the above glass preform.

[0026] An optical instrument contains the above optical glass and / or contains the above optical element.

[0027] The beneficial effects of the present invention are: through reasonable component design, the optical glass of the present invention has excellent weather resistance and internal quality. DETAILED DESCRIPTION

[0028] The following will describe the embodiments of the optical glass of the present invention in detail, but the present invention is not limited to the following embodiments, and can be implemented by appropriate changes within the scope of the purpose of the present invention. In addition, although there are appropriate omissions of descriptions of the repeated descriptions, the gist of the invention will not be limited thereby, and in the following content, the optical glass of the present invention is sometimes referred to as glass.

[0029] [Optical glass]

[0030] The following is an explanation of the range of each component (ingredient) of the optical glass of the present invention. In the present invention, unless otherwise specified, the content and total content of each component are all expressed in weight percentage (wt%), that is, the content and total content of each component are expressed in weight percentage relative to the total amount of glass material converted into oxide composition. Here, the "composition converted into oxide" means that when the oxides, complex salts and hydroxides used as raw materials for the optical glass components of the present invention decompose and transform into oxides during melting, the total amount of the oxide material is taken as 100%.

[0031] Unless otherwise specified in specific circumstances, the numerical ranges listed in the present invention include upper and lower limits, "above" and "below" include endpoint values, and all integers and fractions included in the range, without being limited to the specific values ​​listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.

[0032] <Essential Components and Optional Components>

[0033] SiO2 is the skeleton of optical glass. As a glass network generator, it has the function of maintaining the chemical stability of glass and improving the resistance of glass to devitrification. In the present invention, the above effect is obtained by containing more than 26% SiO2. Preferably, the content of SiO2 is more than 28%, and more preferably, the content of SiO2 is more than 29%. If the content of SiO2 is higher than 36%, the glass meltability is reduced, vitrification is difficult, and it is easy to form stones and other inherent quality problems. At the same time, the transition temperature of the glass rises, and too high a melting temperature will also cause the light transmittance of the glass to deteriorate. Therefore, the upper limit of the content of SiO2 is 36%, preferably 34%, and more preferably 31%.

[0034] B2O3 can improve the melting property and devitrification resistance of glass, but when its content is too high, the chemical stability of glass decreases and the thermal expansion coefficient is adversely affected. Therefore, the content of B2O3 in the present invention is 0-6%, preferably 0.5-5%, and more preferably 1-3%.

[0035] Al2O3 can improve the chemical stability of glass, and increase the mechanical strength and weather resistance of glass, but when its content is too high, the meltability of glass decreases and the anti-crystallization performance deteriorates. Therefore, the content of Al2O3 is 0-8%, preferably 1-7%, and more preferably 2-5%.

[0036] ZrO2 can improve the hardness, refractive index and chemical stability of optical glass, reduce the thermal expansion coefficient of glass, and optimize high-temperature viscosity. When the content of ZrO2 is too high, the resistance to devitrification of glass decreases, the difficulty of melting increases, the melting temperature rises, and inclusions appear inside the glass and the light transmittance decreases. Therefore, the content of ZrO2 in the present invention is 1-10%, preferably 2-8%, and more preferably 3-6%.

[0037] BaO can increase the refractive index of glass, improve the thermal expansion coefficient and high temperature viscosity of glass, but if its content is too high, the chemical stability of glass will be deteriorated. Therefore, the content of BaO is limited to 32-43%, preferably 34-42%, and more preferably 36-40%.

[0038] CaO helps to improve the refractive index and hardness of glass and optimize the abrasiveness of glass, but if the content of CaO is too high, the anti-devitrification performance of glass will decrease. Therefore, the content of CaO is 2-10%, preferably 3-8%, and more preferably 4-7%.

[0039] SrO can adjust the refractive index and Abbe number of glass, but if its content is too high, the chemical stability of the glass will decrease and the cost of the glass will increase rapidly. Therefore, the content of SrO is limited to 0.1-7%, preferably 0.5-5%, and more preferably 1-4%.

[0040] MgO can reduce the relative partial dispersion of glass, but when the MgO content is too high, the refractive index of the glass is difficult to meet the design requirements, and the anti-crystallization performance and stability of the glass are reduced. Therefore, the MgO content is limited to 0-5%, preferably 0-3%, and more preferably 0-1%. In some embodiments, it is further preferred that MgO is not contained.

[0041] TiO2 has the effect of increasing the refractive index and dispersion of glass. A proper amount of TiO2 can make the glass more stable and reduce the viscosity of the glass. If the content of TiO2 is too high, the crystallization tendency of the glass increases and the transition temperature rises. Therefore, the content of TiO2 in the present invention is 0.1-6%, preferably 0.5-5%, and more preferably 0.5-4%.

[0042] In some embodiments, controlling the ratio of TiO2 content to the total content of CaO and Al2O3 CaO+Al2O3 TiO2 / (CaO+Al2O3) in the range of 0.01 to 1.5 is beneficial to reducing the density of the glass and preventing the deterioration of the anti-crystallization performance of the glass. Therefore, preferably TiO2 / (CaO+Al2O3) is 0.01 to 1.5, and more preferably TiO2 / (CaO+Al2O3) is 0.05 to 1.0. Furthermore, controlling TiO2 / (CaO+Al2O3) in the range of 0.1 to 0.8 can also optimize the striation degree of the glass. Therefore, it is further preferred that TiO2 / (CaO+Al2O3) is 0.1 to 0.8, and it is further preferred that TiO2 / (CaO+Al2O3) is 0.1 to 0.5.

[0043] In some embodiments, the ratio (SiO2+SrO) / TiO2 between the total content of SiO2 and SrO SiO2+SrO and the content of TiO2 is controlled to be above 4.5, which can improve the light transmittance and weather resistance of the glass and optimize the striation of the glass. Therefore, it is preferred that (SiO2+SrO) / TiO2 is above 4.5, more preferably (SiO2+SrO) / TiO2 is above 5.0, further preferably (SiO2+SrO) / TiO2 is 6.0 to 32.0, and further preferably (SiO2+SrO) / TiO2 is 7.5 to 20.0.

[0044] ZnO can adjust the refractive index and dispersion of glass, reduce the transition temperature of glass, and allow glass to be melted at a lower temperature, thereby increasing the light transmittance of glass. If the ZnO content is too high, the high-temperature viscosity of the glass will increase, the difficulty of glass molding will increase, and the anti-crystallization performance will deteriorate. Therefore, the ZnO content is 5-15%, preferably 7-13%, and more preferably 9-12%.

[0045] In some embodiments, the ratio (CaO+SrO) / ZnO between the total content of CaO and SrO CaO+SrO and the content of ZnO is controlled within the range of 0.2 to 2.0, which can optimize the light transmittance and high temperature viscosity of the glass and prevent the thermal expansion coefficient of the glass from increasing. Therefore, preferably (CaO+SrO) / ZnO is 0.2 to 2.0, more preferably (CaO+SrO) / ZnO is 0.4 to 1.5, further preferably (CaO+SrO) / ZnO is 0.5 to 1.2, and further preferably (CaO+SrO) / ZnO is 0.7 to 1.0.

[0046] In some embodiments, the ratio (TiO2+ZnO) / CaO between the total content of TiO2 and ZnO TiO2+ZnO and the content of CaO is controlled within the range of 0.6 to 8.0, which can improve the bubble degree and striae degree of the glass and prevent the weather resistance from deteriorating. Therefore, preferably (TiO2+ZnO) / CaO is 0.6 to 8.0, more preferably (TiO2+ZnO) / CaO is 0.8 to 5.0, further preferably (TiO2+ZnO) / CaO is 1.0 to 4.0, and further preferably (TiO2+ZnO) / CaO is 1.5 to 3.0.

[0047] Li2O can lower the transition temperature of glass, adjust the high temperature viscosity of glass, and improve the solubility of glass, but its high content is detrimental to the chemical stability and cost economy of glass. Therefore, the content of Li2O in the present invention is 5% or less, preferably 2% or less, and more preferably 1% or less. In some embodiments, it is further preferred that Li2O is not contained.

[0048] In some embodiments, the ratio of the content of BaO to the total content of SiO2, B2O3, TiO2, and Li2O (SiO2+B2O3+TiO2+Li2O) BaO / (SiO2+B2O3+TiO2+Li2O) is controlled within the range of 0.65 to 1.2, which can improve the hardness and striae of the glass and reduce the thermal expansion coefficient of the glass. Therefore, preferably, BaO / (SiO2+B2O3+TiO2+Li2O) is 0.65 to 1.2, more preferably, BaO / (SiO2+B2O3+TiO2+Li2O) is 0.7 to 1.1, further preferably, BaO / (SiO2+B2O3+TiO2+Li2O) is 0.75 to 1.05, and further preferably, BaO / (SiO2+B2O3+TiO2+Li2O) is 0.8 to 1.05.

[0049] Na2O has the function of improving the fusibility of glass and can improve the melting effect of glass. If the content of Na2O is too high, the chemical stability and weather resistance of glass will be reduced. Therefore, the content of Na2O is 0.1-7%, preferably 1-6%, and more preferably 2-5%.

[0050] In some embodiments, controlling the ratio of the content of B2O3 to the content of Na2O, B2O3 / Na2O, to be below 8.0 can prevent the chemical stability of the glass from deteriorating. Therefore, preferably B2O3 / Na2O is below 8.0. Further, controlling B2O3 / Na2O to be within the range of 0.05 to 5.0 can further optimize the high temperature viscosity and bubble degree of the glass. Therefore, more preferably B2O3 / Na2O is 0.05 to 5.0, further preferably B2O3 / Na2O is 0.1 to 4.0, and further preferably B2O3 / Na2O is 0.2 to 2.0.

[0051] In some embodiments, the ratio of TiO2 to Na2O is controlled within the range of 0.02 to 5.0, which can prevent the transition temperature from increasing while optimizing the anti-crystallization performance and striae of the glass. Therefore, TiO2 / Na2O is preferably 0.02 to 5.0, more preferably 0.05 to 3.0, further preferably 0.1 to 2.0, and further preferably 0.3 to 1.5.

[0052] In some embodiments, the ratio of SiO2 to the total content of Na2O and BaO Na2O+BaO SiO2 / (Na2O+BaO) is controlled within the range of 0.55 to 0.95, which can reduce the thermal expansion coefficient and density of the glass while improving the weather resistance of the glass. Therefore, preferably SiO2 / (Na2O+BaO) is 0.55 to 0.95, more preferably SiO2 / (Na2O+BaO) is 0.55 to 0.9, more preferably SiO2 / (Na2O+BaO) is 0.6 to 0.85, and even more preferably SiO2 / (Na2O+BaO) is 0.65 to 0.8.

[0053] K2O has the effect of improving the thermal stability and melting property of glass, but if its content exceeds 5%, the devitrification resistance and chemical stability of glass deteriorate. Therefore, the content of K2O in the present invention is 0-5%, preferably 0-2%, more preferably 0-1%. In some embodiments, it is further preferred that K2O is not contained.

[0054] In some embodiments, the ratio (SiO2+BaO) / (Li2O+Na2O+K2O+TiO2) between the total content of SiO2 and BaO SiO2+BaO and the total content of Li2O, Na2O, K2O, and TiO2 Li2O+Na2O+K2O+TiO2 is controlled to be above 6.0, which can improve the anti-crystallization performance of the glass and prevent the transition temperature of the glass from increasing. Therefore, it is preferred that (SiO2+BaO) / (Li2O+Na2O+K2O+TiO2) is above 6.0, and it is more preferred that (SiO2+BaO) / (Li2O+Na2O+K2O+TiO2) is above 8.3. Furthermore, by controlling (SiO2+BaO) / (Li2O+Na2O+K2O+TiO2) within the range of 9.0 to 50.0, the thermal expansion coefficient and high temperature viscosity of the glass can be further optimized. Therefore, it is further preferred that (SiO2+BaO) / (Li2O+Na2O+K2O+TiO2) is 9.0 to 50.0, and it is further preferred that (SiO2+BaO) / (Li2O+Na2O+K2O+TiO2) is 10.0 to 30.0.

[0055] Nb2O5 can increase the refractive index of glass, improve the chemical stability and resistance to devitrification of glass, but if its content is too high, the dispersion of glass will increase, and it will be difficult to obtain glass with target optical constants. At the same time, the cost and density of glass will increase, and the short-wave transmittance in the visible light region will decrease. Therefore, the content of Nb2O5 in the present invention is 5% or less, preferably 2% or less, and more preferably 1% or less. In some embodiments, it is further preferred that Nb2O5 is not contained.

[0056] WO3 can improve the refractive index and mechanical strength of glass. If the content of WO3 exceeds 5%, the thermal stability of glass decreases and the resistance to devitrification decreases. Therefore, the upper limit of WO3 content is 5%, preferably 2%, and more preferably 1%. In some embodiments, it is further preferred that WO3 is not contained.

[0057] Ln2O3 (Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3) is a component that improves the refractive index and chemical stability of glass. By controlling the content of Ln2O3 to 5% or less, the devitrification resistance of glass can be prevented from decreasing. The upper limit of the Ln2O3 content is preferably 2%, and the upper limit is more preferably 1%. In some embodiments, it is further preferred that Ln2O3 is not contained.

[0058] In some embodiments, controlling Ln2O3 / TiO2 to be below 0.5 can prevent the weather resistance and chemical stability of the glass from being reduced and optimize the high temperature viscosity of the glass. Therefore, Ln2O3 / TiO2 is preferably below 0.5, more preferably below 0.4, further preferably below 0.3, and further preferably below 0.1.

[0059] In some embodiments, the ratio (B2O3+Ln2O3) / ZrO2 between the total content of B2O3 and Ln2O3 B2O3+Ln2O3 and the content of ZrO2 is controlled to be below 1.8, which can prevent the chemical stability of the glass from deteriorating while lowering the transition temperature of the glass. Therefore, it is preferred that (B2O3+Ln2O3) / ZrO2 is below 1.8, and it is more preferred that (B2O3+Ln2O3) / ZrO2 is below 1.5. Furthermore, by controlling (B2O3+Ln2O3) / ZrO2 within the range of 0.05 to 1.2, the bubble degree of the glass can be further optimized. Therefore, it is further preferred that (B2O3+Ln2O3) / ZrO2 is 0.05 to 1.2, and it is further preferred that (B2O3+Ln2O3) / ZrO2 is 0.1 to 1.0.

[0060] In the present invention, by containing 0-1% of one or more components of Sb2O3, SnO, SnO2, and CeO2 as a clarifier, the clarification effect of the glass can be improved and the bubble degree of the glass can be improved. The content of the clarifier is preferably 0-0.5%, and the content of the clarifier is more preferably 0-0.2%. Sb2O3 is preferably used as a clarifier. When the content of Sb2O3 exceeds 1%, the clarification performance of the glass tends to decrease. At the same time, due to its strong oxidizing effect, it promotes the corrosion of the platinum or platinum alloy vessel for melting glass and the deterioration of the forming mold. Therefore, the content of Sb2O3 in the present invention is preferably 0-1%, more preferably 0-0.5%, and further preferably 0-0.2%. SnO and SnO2 can also be used as clarifiers, but when their content exceeds 1%, the tendency of the glass to color increases, or when the glass is heated, softened, and molded again, Sn will become the starting point of crystal nucleation, resulting in a tendency to devitrification. Therefore, the content of SnO2 in the present invention is preferably 0-1%, more preferably 0-0.5%, further preferably 0-0.2%, and further preferably does not contain SnO2; the content of SnO is preferably 0-1%, more preferably 0-0.5%, further preferably 0-0.2%, and further preferably does not contain SnO. The role and content ratio of CeO2 are consistent with those of SnO2, and its content is preferably 0-1%, more preferably 0-0.5%, further preferably 0-0.2%, and further preferably does not contain CeO2.

[0061] <Components that should not be contained>

[0062] In the glass of the present invention, even if oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo are contained alone or in combination in small amounts, the glass will be colored and absorption will occur at specific wavelengths in the visible light region, thereby weakening the property of the present invention of improving the visible light transmittance. Therefore, it is preferably substantially free of oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo, especially for optical glasses that require transmittance at wavelengths in the visible light region.

[0063] The oxides of Th, Cd, Tl, Os, Be and Se have a tendency to be controlled in recent years as harmful chemical substances, and environmental protection measures are necessary not only in the manufacturing process of glass, but also in the processing process and the disposal after productization. Therefore, in the case of paying attention to the impact on the environment, it is preferred that they are not actually contained except for being inevitably mixed in. Thus, the optical glass does not actually contain substances that pollute the environment. Therefore, even if special environmental countermeasures are not taken, the optical glass of the present invention can be manufactured, processed and discarded.

[0064] In order to achieve environmental friendliness, the optical glass of the present invention preferably does not contain As2O3 and PbO.

[0065] The "does not contain" and "0%" recorded in this article mean that the compound, molecule or element is not intentionally added as a raw material to the optical glass of the present invention; however, as raw materials and / or equipment for producing optical glass, there will be certain impurities or components that are not intentionally added, which will be contained in a small amount or trace amount in the final optical glass, and this situation is also within the scope of protection of the patent of this invention.

[0066] Next, the properties of the optical glass of the present invention will be described.

[0067] <Refractive Index and Abbe Number>

[0068] The refractive index of optical glass (n d ) and the Abbe number (ν d ) Tested according to the method specified in GB / T 7962.1-2010.

[0069] In some embodiments, the refractive index (n d ) has a lower limit of 1.64, a preferred lower limit is 1.65, and a more preferred lower limit is 1.66.

[0070] In some embodiments, the refractive index (n d ) is 1.695, preferably 1.69, and more preferably 1.68.

[0071] In some embodiments, the Abbe number (ν d ) has a lower limit of 45.5, a preferred lower limit of 46, and a more preferred lower limit of 47.

[0072] In some embodiments, the Abbe number (ν d ) has an upper limit of 51.5, a preferred upper limit of 50, and a more preferred upper limit of 49.

[0073] <density>

[0074] The density (ρ) of optical glass is tested according to the method specified in GB / T7962.20-2010.

[0075] In some embodiments, the density (ρ) of the optical glass of the present invention is 4.00 g / cm 3 Below, preferably 3.90g / cm 3 Below, more preferably 3.85g / cm 3 the following.

[0076] <Coefficient of Thermal Expansion>

[0077] Thermal expansion coefficient of optical glass (α 100 / 300℃ ) The data at 100-300℃ were tested according to the method specified in GB / T7962.16-2010.

[0078] In some embodiments, the thermal expansion coefficient (α 100 / 300℃ ) is 100×10 -7 / K or less, preferably 98×10 -7 / K or less, more preferably 95×10 -7 / K or less.

[0079] <Water resistance stability>

[0080] Water resistance stability of optical glass (D W ) (Powder method) Tested in accordance with the method specified in GB / T 17129.

[0081] In some embodiments, the water resistance stability (D W ) is 3 or more, preferably 2 or more.

[0082] <Weather resistance>

[0083] The test method for weather resistance (CR) of optical glass is as follows: place the sample in a test box with a saturated water vapor environment of 90% relative humidity, alternately cycle every 1 hour at 40-50°C, and cycle for 15 cycles. The weather resistance category is divided according to the change in turbidity before and after the sample is placed. The weather resistance classification is shown in Table 1:

[0084] Table 1.

[0085]

[0086] In some embodiments, the weather resistance (CR) of the optical glass of the present invention is Class 2 or higher, preferably Class 1.

[0087] <Bubble Degree>

[0088] The bubble degree of optical glass is tested according to the method specified in GB / T7962.8-2010.

[0089] In some embodiments, the bubble degree of the optical glass of the present invention is above grade A, preferably above grade A0, and more preferably above grade A1. 00 class.

[0090] <Transition Temperature>

[0091] Transition temperature of optical glass (T g ) The test shall be carried out in accordance with the method specified in GB / T7962.16-2010.

[0092] In some embodiments, the transition temperature (T g ) is 660°C or lower, preferably 650°C or lower, and more preferably 640°C or lower.

[0093] <Anti-devitrification>

[0094] The test method for anti-crystallization performance is as follows: cut the sample glass into 20×20×10mm specifications and place it in a g Keep the glass in a muffle furnace at +(200-250)℃ for 15-30 minutes, take it out and cool it down, and then observe whether there are crystals or opacity on the surface and inside of the glass. If the glass sample has no opacity and / or crystals, the glass has excellent anti-crystallization performance. This test method is used to characterize the anti-crystallization performance of the secondary pressing glass of the present invention.

[0095] <Striation Degree>

[0096] The striation degree of the glass of the present invention is measured according to the method specified in MLL-G-174B. The method is to use a striation meter composed of a point light source and a lens, and compare and inspect with a standard sample from the direction where the striations are most easily visible. There are 4 levels in total, namely A, B, C, and D. Level A means no striations visible to the naked eye under the specified detection conditions, level B means fine and scattered striations under the specified detection conditions, level C means slight parallel striations under the specified detection conditions, and level D means rough striations under the specified detection conditions.

[0097] In some embodiments, the striae degree of the optical glass of the present invention is C level or higher, preferably B level or higher.

[0098] <High temperature viscosity>

[0099] The high temperature viscosity of optical glass is tested by the following method: The high temperature viscosity of glass is tested using THETA Rheotronic II high temperature viscometer using a rotation method. The unit of value is dPaS (poise). The smaller the value, the lower the viscosity.

[0100] In some embodiments, the viscosity of the optical glass of the present invention at 1400° C. is 60 poise or less, preferably 1 to 50 poise, and more preferably 2 to 30 poise.

[0101] <Light transmittance>

[0102] Light transmittance of optical glass (τ 400nm ) The test shall be carried out according to the method specified in GB / T 7962.12-2010.

[0103] In some embodiments, the optical glass of the present invention has a light transmittance (τ 400nm ) is 95.0% or more, preferably 96.0% or more, more preferably 97.0% or more, and further preferably 98.0% or more.

[0104] [Method for producing optical glass]

[0105] The manufacturing method of the optical glass of the present invention is as follows: the glass of the present invention is produced using conventional raw materials and processes, including but not limited to using oxides, hydroxides, complex salts (such as carbonates, nitrates, sulfates, etc.), boric acid, etc. as raw materials, and after the ingredients are prepared according to the conventional method, the prepared furnace materials are put into a melting furnace (such as platinum or platinum alloy crucible) at 1200-1400°C for melting, and after clarification and homogenization, a homogeneous molten glass without bubbles and undissolved substances is obtained, and the molten glass is cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods and process parameters according to actual needs.

[0106] [Glass preforms and optical components]

[0107] The prepared optical glass can be used to make a glass preform by means of direct drop molding, grinding, or compression molding such as hot press molding. That is, the molten optical glass can be directly precision drop molded into a glass precision preform, or the glass preform can be made by mechanical processing such as grinding and grinding, or the preform for compression molding made of the optical glass can be made by hot press molding and then grinding. It should be noted that the means for preparing the glass preform are not limited to the above means.

[0108] As described above, the optical glass of the present invention is useful for various optical elements and optical designs, and it is particularly preferred to form a preform from the optical glass of the present invention and use the preform to perform re-hot pressing, precision stamping, etc. to produce optical elements such as lenses and prisms.

[0109] The glass preform and optical element of the present invention are both formed of the optical glass of the present invention. The glass preform of the present invention has the excellent properties of optical glass; the optical element of the present invention has the excellent properties of optical glass, and can provide various optical elements such as lenses and prisms with high optical value.

[0110] Examples of the lens include various lenses having spherical or aspherical lens surfaces, such as a concave meniscus lens, a convex meniscus lens, a biconvex lens, a biconcave lens, a plano-convex lens, and a plano-concave lens.

[0111] [Optical instruments]

[0112] The optical element formed by the optical glass of the present invention can be used to manufacture optical instruments such as photographic equipment, video equipment, projection equipment, display equipment, vehicle-mounted equipment and monitoring equipment.

[0113] Example

[0114] <Optical Glass Example>

[0115] In order to further clearly illustrate and describe the technical solution of the present invention, the following non-limiting examples are provided.

[0116] This embodiment adopts the manufacturing method of the above optical glass to obtain an optical glass having the composition shown in Table 2 to Table 4. In addition, the characteristics of each glass are measured by the test method described in the present invention, and the measurement results are shown in Table 2 to Table 4. In the anti-crystallization performance test of Table 2 to Table 4, according to the aforementioned test method, the glass without opacity and without crystal particles on the surface and inside is recorded as "A", without opacity and without crystallization particles inside but with crystallization particles on the surface is recorded as "B" (when the glass is pressed twice, the crystallization particles on the surface can be removed by grinding, but the grinding cost will increase, so the glass composition with no crystallization particles inside and outside the glass is more preferred), without opacity but with 1 to 10 crystal particles inside is recorded as "C", without opacity but with 10 to 20 crystal particles inside is recorded as "D", and opacity or dense crystallization particles inside are recorded as "×".

[0117] Table 2.

[0118]

[0119]

[0120] Table 3.

[0121]

[0122]

[0123] Table 4.

[0124]

[0125]

[0126] <Glass Preform Example>

[0127] The glass obtained from optical glass examples 1 to 20# is used, for example, by grinding processing, or by molding methods such as hot pressing, precision stamping, etc., to make preforms of various lenses, prisms, etc., such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses.

[0128] <Optical Element Embodiment>

[0129] The preforms obtained in the above-mentioned glass preform embodiments are annealed to reduce the internal stress of the glass and fine-tune the refractive index so that the optical properties such as the refractive index reach the desired values.

[0130] Next, each preform is ground and polished to produce various lenses and prisms such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. The surface of the obtained optical element may be coated with an anti-reflection film.

[0131] <Optical Instrument Embodiment>

[0132] The optical element obtained by the above-mentioned optical element embodiment is optically designed to form an optical component or optical assembly by using one or more optical elements, and can be used in, for example, imaging equipment, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, lithography technology, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices including such circuits and chips.

Claims

1. Optical glass, It is characterized in that Its components contain SiO 2 、ZrO 2 ,BaO,CaO,TiO 2 and ZnO, the components are expressed in weight percentage, among which (TiO 2 + ZnO) / CaO is 0.6 to 8.0, and the refractive index of the optical glass n d 1.64~1.695, Abbe number ν d The temperature is 45.5-51.5, the weather resistance CR is 2 or above, and the bubble degree is A or above.

2. The optical glass according to claim 1, It is characterized in that Its components are expressed in weight percentages and contain: SiO 2 : 26 - 36%; and / or Al 2 O 3 : 0 - 8%; and / or ZrO 2 : 1 - 10%; and / or BaO: 32 - 43%; and / or CaO: 2 - 10%; and / or SrO: 0.1 - 7%; and / or TiO 2 : 0.1 - 6%; and / or ZnO: 5 - 15%; and / or Na 2 O: 0.1 - 7%; and / or B 2 O 3 : 0 - 6%; and / or MgO: 0 - 5%; and / or Li 2 O: 0 - 5%; and / or K 2 O: 0 - 5%; and / or WO 3 : 0 - 5%; and / or Nb 2 O 5 : 0 - 5%; and / or Ln 2 O 3 : 0 - 5%; and / or clarifying agent: 0 - 1%, where the Ln 2 O 3 is La 2 O 3 、Gd 2 O 3 、Y 2 O 3 、Yb 2 O 3 、Lu 2 O 3 and one or more of them, and the clarifying agent is Sb 2 O 3 、SnO、SnO 2 、CeO 2 and one or more of them.

3. Optical glass, It is characterized in that Its components are expressed in weight percentage, consisting of SiO 2 :26~36%;Al 2 O 3 :0~8%;ZrO 2 : 1~10%; BaO: 32~43%; CaO: 2~10%; SrO: 0.1~7%; TiO 2 :0.1~6%; ZnO: 5~15%;Na 2 O: 0.1~7%;B 2 About 3 :0~6%; MgO:0~5%;Li 2 O:0~5%;K 2 O:0~5%;WO 3 :0~5%;Nb 2 O 5 :0~5%;Ln 2 O 3 :0~5%; Clarifier: 0-1%, including (TiO 2 + ZnO) / CaO is 0.6-8.0, and the Ln 2 O 3 For La 2 O 3 , Gd 2 O 3 , Y 2 O 3 , Yb 2 O 3 、Lu 2 O 3 One or more of the following, the clarifier is Sb 2 O 3 、SnO、SnO 2 、CeO 2 One or more of .

4. The optical glass according to any one of claims 1 to 3, It is characterized in that Its components are expressed in weight percentage and meet one or more of the following 11 conditions: 1) TiO 2 / (CaO+Al 2 O 3 ) is 0.01 to 1.5, preferably TiO 2 / (CaO+Al 2 O 3 ) is 0.05 to 1.0, and more preferably TiO 2 / (CaO+Al 2 O 3 ) is 0.1 to 0.8, and TiO 2 / (CaO+Al 2 O 3 ) is 0.1 to 0.5; 2)(SiO 2 +SrO) / TiO 2 4.5 or more, preferably (SiO 2 +SrO) / TiO 2 5.0 or more, more preferably (SiO 2 +SrO) / TiO 2 6.0 to 32.0, more preferably (SiO 2 +SrO) / TiO 2 7.5~20.0; 3) (CaO + SrO) / ZnO is 0.2 to 2.0, preferably (CaO + SrO) / ZnO is 0.4 to 1.5, more preferably (CaO + SrO) / ZnO is 0.5 to 1.2, and further preferably (CaO + SrO) / ZnO is 0.7 to 1.0; 4)(TiO 2 + ZnO) / CaO is 0.8 to 5.0, preferably (TiO 2 + ZnO) / CaO is 1.0 to 4.0, and more preferably (TiO 2 + ZnO) / CaO is 1.5 to 3.0; 5) B 2 O 3 / Na 2 O is 8.0 or less, preferably B 2 O 3 / Na 2 O is 0.05 to 5.0, more preferably B 2 O 3 / Na 2 O is 0.1 to 4.0, and B is more preferred 2 O 3 / Na 2 O is 0.2 to 2.0; 6) TiO 2 / Na 2 O is 0.02 to 5.0, preferably TiO 2 / Na 2 O is 0.05 to 3.0, more preferably TiO 2 / Na 2 O is 0.1 to 2.0, and more preferably TiO 2 / Na 2 O is 0.3 to 1.5; 7) SiO 2 / (Na 2 O+BaO) is 0.55 to 0.95, preferably SiO 2 / (Na 2 O+BaO) is 0.55 to 0.9, more preferably SiO 2 / (Na 2 O+BaO) is 0.6 to 0.85, and SiO is more preferred 2 / (Na 2 O+BaO) is 0.65~0.8; 8)BaO / (SiO 2 +B 2 O 3 +TiO 2 +Li 2 O) is 0.65 to 1.2, preferably BaO / (SiO 2 +B 2 O 3 +TiO 2 +Li 2 O) is 0.7 to 1.1, and BaO / (SiO 2 +B 2 O 3 +TiO 2 +Li 2 O) is 0.75 to 1.05, and BaO / (SiO 2 +B 2 O 3 +TiO 2 +Li 2 O) is 0.8 to 1.05; 9)(SiO 2 +BaO) / (Li 2 O+Na 2 O+K 2 O+TiO 2 ) is 6.0 or more, preferably (SiO 2 +BaO) / (Li 2 O+Na 2 O+K 2 O+TiO 2 ) is 8.3 or more, more preferably (SiO 2 +BaO) / (Li 2 O+Na 2 O+K 2 O+TiO 2 ) is 9.0 to 50.0, and more preferably (SiO 2 +BaO) / (Li 2 O+Na 2 O+K 2 O+TiO 2 ) is 10.0~30.0; 10) Ln 2 O 3 / TiO 2 0.5 or less, preferably Ln 2 O 3 / TiO 2 0.4 or less, more preferably Ln 2 O 3 / TiO 2 is 0.3 or less, and more preferably Ln 2 O 3 / TiO 2 is below 0.1; 11)(B 2 O 3 +Ln 2 O 3 ) / ZrO 2 is 1.8 or less, preferably (B 2 O 3 +Ln 2 O 3 ) / ZrO 2 is 1.5 or less, more preferably (B 2 O 3 +Ln 2 O 3 ) / ZrO 2 is 0.05 to 1.2, and more preferably (B 2 O 3 +Ln 2 O 3 ) / ZrO 2 is 0.1 to 1.0, and the Ln 2 O 3 For La 2 O 3 , Gd 2 O 3 , Y 2 O 3 , Yb 2 O 3 、Lu 2 O 3 One or more of .

5. The optical glass according to any one of claims 1 to 3, It is characterized in that Its components are expressed in weight percentage, among which: SiO 2 : 28-34%, preferably SiO 2 : 29-31%; and / or Al 2 O 3 : 1-7%, preferably Al 2 O 3 :2~5%; and / or ZrO 2 : 2-8%, preferably ZrO 2 : 3-6%; and / or BaO: 34-42%, preferably BaO: 36-40%; and / or CaO: 3-8%, preferably CaO: 4-7%; and / or SrO: 0.5-5%, preferably SrO: 1-4%; and / or TiO 2 : 0.5-5%, preferably TiO 2 : 0.5-4%; and / or ZnO: 7-13%, preferably ZnO: 9-12%; and / or Na 2 O: 1-6%, preferably Na 2 O: 2-5%; and / or B 2 O 3 : 0.5-5%, preferably B 2 O 3 : 1-3%; and / or MgO: 0-3%, preferably MgO: 0-1%; and / or Li 2 O: 0-2%, preferably Li 2 O: 0-1%; and / or K 2 O: 0-2%, preferably K 2 O: 0~1%; and / or WO 3 : 0-2%, preferably WO 3 :0~1%;and / or Nb 2 O 5 : 0-2%, preferably Nb 2 O 5 :0~1%;and / or Ln 2 O 3 : 0-2%, preferably Ln 2 O 3 : 0-1%; and / or clarifier: 0-0.5%, preferably clarifier: 0-0.2%, the Ln 2 O 3 For La 2 O 3 , Gd 2 O 3 , Y 2 O 3 , Yb 2 O 3 、Lu 2 O 3 One or more of the following, the clarifier is Sb 2 O 3 、SnO、SnO 2 、CeO 2 One or more of .

6. The optical glass according to any one of claims 1 to 3, It is characterized in that Its composition does not contain MgO; and / or does not contain Li 2 O; and / or does not contain K 2 O; and / or does not contain WO 3 ; and / or does not contain Nb 2 O 5 ; and / or does not contain SnO 2 ; and / or does not contain SnO; and / or does not contain CeO 2 ; and / or does not contain As 2 O 3 ; and / or does not contain PbO; and / or does not contain Ln 2 O 3 , the Ln 2 O 3 For La 2 O 3 , Gd 2 O 3 , Y 2 O 3 , Yb 2 O 3 、Lu 2 O 3 One or more of .

7. The optical glass according to any one of claims 1 to 3, It is characterized in that The refractive index n of the optical glass d is 1.64 to 1.695, preferably 1.65 to 1.69, more preferably 1.66 to 1.68, and the Abbe number v d It is 45.5-51.5, preferably 46-50, more preferably 47-49.

8. The optical glass according to any one of claims 1 to 3, It is characterized in that The density of the optical glass is 4.00 g / cm 3 Below, preferably 3.90g / cm 3 Below, more preferably 3.85g / cm 3 Below; and / or thermal expansion coefficient α 100 / 300℃ 100×10 -7 / K or less, preferably 98×10 -7 / K or less, more preferably 95×10 -7 / K or less; and / or water resistance stability D W 3 or more, preferably 2 or more; and / or weather resistance CR is 2 or more, preferably 1; and / or bubble degree is A or more, preferably A 0 Grade A or above, preferably A 00 level; and / or transition temperature T g 660°C or less, preferably 650°C or less, more preferably 640°C or less; and / or the striae is C or above, preferably B or above; and / or the viscosity at 1400°C is 60 poise or less, preferably 1 to 50 poise, more preferably 2 to 30 poise; and / or the light transmittance τ 400nm It is 95.0% or more, preferably 96.0% or more, more preferably 97.0% or more, and further preferably 98.0% or more.

9. Glass preforms, It is characterized in that Made of the optical glass described in any one of claims 1 to 8.

10. Optical components, It is characterized in that The optical glass is made of the optical glass described in any one of claims 1 to 8, or the glass preform described in claim 9.

11. Optical instruments, It is characterized in that Contains the optical glass according to any one of claims 1 to 8, and / or contains the optical element according to claim 10.